Microwave-assisted synthesis and characterization of undoped and manganese doped zinc sulfide nanoparticles - Kuzmin, Alexei; Dile, Milena; Laganovska, Katrina; Zolotarjovs, Aleksejs (Elsevier, 2022)
Undoped and Mn-doped ZnS nanocrystals were produced by the microwave-assisted solvothermal method and characterized by X-ray diffraction, photoluminescence spectroscopy and scanning electron microscopy with energy-dispersive X-ray spectroscopy. All samples have the cubic zinc blende structure with the lattice parameter in the range of a = 5.406–5.411 Å, and the average size of crystallites is in the range of 6–9 nm. These nanoparticles agglomerate and form large grains with an average size of up to 180 nm. The photoluminescence of the undoped ZnS sample shows a broad emission band located at 530 nm, attributed to the defects at the surface of nanoparticles. In all Mn-doped samples, the emission peak at 598 nm was observed assigned to the characteristic forbidden transition between excited (4T1) and ground (6A1) levels of Mn2+. Synchrotron radiation X-ray absorption spectroscopy at the Zn and Mn K-edges combined with reverse Monte Carlo (RMC) simulations based on the evolutionary algorithm confirms that manganese ions substitute zinc ions. However, the difference in the ion sizes (R(Mn2+(IV)) = 0.66 Å and R(Zn2+(IV)) = 0.60 Å) is responsible for the larger interatomic distances Mn–S (2.40(2) Å) compared to Zn–S (2.33(2) Å). The static structural relaxations in ZnS:Mn nanoparticles are responsible for the large values of the mean-square displacements factors for Zn, S and Mn atoms obtained by RMC simulations.--//-- This is a preprint of the article A. Kuzmin, M. Dile, K. Laganovska, A. Zolotarjovs, Microwave-assisted synthesis and characterization of undoped and manganese doped zinc sulfide nanoparticles, Mater. Chem. Phys. 290 (2022) 126583. Doi: 10.1016/j.matchemphys.2022.126583. The article is published under the CC BY-NC-ND licence.
The financial support of the European Regional Development Fund (ERDF) Project No. 1.1.1.1/20/A/060 is greatly acknowledged. We acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. Parts of this research were carried out at PETRA III and we would like to thank Dr. Edmund Welter for assistance in using P65 beamline. Beamtime was allocated for proposal I-20210366 EC. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; ZnS:Mn; X-ray diffraction; Scanning electron microscopy; Photoluminescence spectroscopy; X-ray absorption spectroscopy